Impact of Lockdown of COVID 19 Pandemic in Pregnancy Outcomes in a Tertiary Care Centre: What to Expect? - Subedi, Anjali; Magar, Poonam; Shrestha, Junu; Subedi, Seema (Journal of Lumbini Medical College, 2021)
Introduction: Corona Virus Disease 19 (COVID-19) was declared a "pandemic" in March 2020 by WHO and advocated lockdown measures with the use of mask, frequent hand washing and social distancing for decreasing the transmission of disease. In Nepal where antenatal coverage is just 50% and institutional deliveries 54%, this lockdown has further reduced the regular antenatal visits, institutional deliveries posing an increased adverse effect in pregnancy outcome. This study aimed to reveal the impact of lockdown of COVID 19 pandemic in pregnancy outcomes in a tertiary care center. Methods: It was a cross-sectional, analytical study done in the Department of Obstetrics and Gynecology, Manipal Teaching Hospital for three months lockdown period (March 2020 to June 2020) and total deliveries along with maternal and perinatal complications were studied in the lockdown period and compared with those in non-lockdown period. Results: During the lockdown period, there were total 1070 deliveries and maternal complication was seen in 17.38% of deliveries. In the non-lockdown period, there were total of 982 deliveries and maternal complication was present in 18.43% of deliveries (p= 0.53). In the study, more cases of early pregnancy complications were seen in lockdown period than in non-lockdown period. Regarding obstetric complications, hypertensive disorder was the most common one observed during lockdown period whereas preterm labor was common in non-lockdown period. There was no increase in perinatal complications during lockdown period on comparing to non-lockdown period. Conclusion: There was no increase in adverse pregnancy outcomes during lockdown of COVID 19 pandemic in a tertiary care center.